23. EFFECTIVENESS AND SAFETY OF MICROSURGICAL VARICOCELECTOMY THROUGH 3 YEARS AT 19-8 HOSPITAL, MINISTRY OF PUBLIC SECURITY, FROM 2020 TO 2023 (Vietnam Journal of Community Medicine, 2024)
Objectives: Description of the effectiveness and the safety of microsurgical varicocelectomy at 19-8 Hospital, Ministry of Public Security, from 2020 to 2023.Methods: Descriptive, prospective follow-up study of a case series includes 160 patients that have undergone microsurgical varicocelectomy at 19-8 hospital, ministry of public security from 12/2020 to 12/2023.Results: The mean age of patients was 23.81±5.91 years old. The proportion of scrotal pain was 96.9% and the figure of that varicose veins are palpable in the scrotum was 75%. The success and failure rate of this surgery were 96.25% and 3.75%, respectively. Before surgery, the diameters of the seminal veins before and after the Valsalva test were 2.93±0.54mm and 3.59±0.61mm, respectively. After surgery 3 months, these diameters remarkably decreased at 1.70 ± 0.54mm and 1.97 ± 0.54mm, with statistical significance p < 0.05. The semen chart after surgery improved significantly, in which the percentage of motile spermatozoa after surgery 3 months was 42.03 ± 12.55%, higher than the rate before surgery was 35.59 ± 11.53%, total sperm count after surgery was 192.003 ± 179.114 million that was increased in compared with the figure before surgery was 111.003 ± 134.468 million sperm, the sperm concentration before surgery was 30.81 ± 26.58 and this figure after 3 months increased to 47.30 ± 35.21.Conclusion: Microsurgical varicocelectomy is a safe and effective method in the treatment of varicocele patients that have surgical indication.
Keywords: Varicocele, microsurgical varicocelectomy.